2017
DOI: 10.4236/ss.2017.88038
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vs. Robotic Approach to Partial Colon Resection

Abstract: We retrospectively collected data on 130 minimally invasive colon resection cases performed by the same surgeon from April 2005 to February 2017, of which 35 were completed laparoscopically and 95 were completed robotically. The first 30 robotic cases were allocated to a Training group to account for the learning needed to stabilize operative ability. The 35 laparoscopic cases and 65 of the 95 robotic cases, starting with the 31 st case, were compared. Robotic partial colon resection was significantly more cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Three studies identified a significantly lower rate of conversion during RRH . This finding has been documented in many studies identifying a robotic approach to be significantly associated with lower conversion rates to open . Furthermore, although examining outcomes in RRH compared to LRH for both oncological and benign lesions, a systematic review and meta‐analysis by Solaini et al .…”
Section: Discussionmentioning
confidence: 86%
“…Three studies identified a significantly lower rate of conversion during RRH . This finding has been documented in many studies identifying a robotic approach to be significantly associated with lower conversion rates to open . Furthermore, although examining outcomes in RRH compared to LRH for both oncological and benign lesions, a systematic review and meta‐analysis by Solaini et al .…”
Section: Discussionmentioning
confidence: 86%